2019
DOI: 10.32872/spb.v14i1.33507
|View full text |Cite
|
Sign up to set email alerts
|

Contingencies of Self-Worth and Global Self-Esteem Among College Women: The Role of Masculine and Feminine Traits Endorsement

Abstract: The study examined the relative importance of seven contingencies of self-worth of Polish college women's (appearance, others' approval, competition, academic competencies, family support, virtue, God's love), as well as the associations between preference for particular contingencies and global self-esteem. Additionally, the predictive role of the self-assignment of masculine and feminine traits for both contingencies of self-worth and global self-esteem was investigated. The participants were one hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…Our present research corroborates these findings, with adolescent girls scoring higher on this measure than boys. Research on the relation between gender role self-concept and academic contingent self-esteem is scarce, though one study using an adult sample found no association between these constructs (Mandal & Moroń, 2019). We hypothesized that students who see themselves as having more instrumental characteristics may also place less importance on academic pursuits.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our present research corroborates these findings, with adolescent girls scoring higher on this measure than boys. Research on the relation between gender role self-concept and academic contingent self-esteem is scarce, though one study using an adult sample found no association between these constructs (Mandal & Moroń, 2019). We hypothesized that students who see themselves as having more instrumental characteristics may also place less importance on academic pursuits.…”
Section: Discussionmentioning
confidence: 90%
“…However, the relation between gender role self-concept and contingent selfesteem is less established. An investigation on women in Poland did not find an association between masculinity, as measured by an adaptation of the BSRI (Bem, 1974), and academic contingent self-esteem (Mandal & Moroń, 2019), but research with adolescents in schools is needed.…”
Section: Academic Contingent Self-esteemmentioning
confidence: 98%
“…Religious people in religious cultures self-enhance in areas essential to their self-concept more than their counterparts in secular cultural contexts (Sedikides and Gebauer 2020;Joshanloo and Gebauer 2019). In a Polish sample, experience of God's love was one of the conditions for self-esteem in women (Mandal and Moroń 2019). On the other hand, some studies suggest that individuals who are more religiously involved have less positive self-worth (Krause 1995).…”
Section: Religiosity Anger and Self-dignitymentioning
confidence: 99%